Chapter «Il Vangelo mi prende alla gola». Gli alfabeti filosofico-religiosi in Claudio Magris - Fiume, Valentina (Biblioteca di Studi di Filologia Moderna, 2021)
The essay deals with a still-unexplored field in Claudio Magris' writing, which is also the highest dimension of his work, namely, the philosophical-religious alphabets.